Second-Pandemic Strain of Vibrio cholerae from the Philadelphia Cholera Outbreak of 1849 - Devault, Alison M; Golding, G. Brian; Waglechner, Nicholas; Enk, Jacob M; Kuch, Melanie; Tien, Joseph H; Shi, Mang; Fisman, David N; Dhody, Anna N; Forrest, Stephen; Bos, Kirsten I; Earn, David J.D; et al. (The New England journal of medicine, 2014)
A draft genome of a second-pandemic V. cholerae strain was reconstructed with the use of a museum specimen from a victim of the 1849 cholera outbreak in Philadelphia. This strain was found to be of the O1 classical biotype. Cholera is a diarrheal disease caused by colonization of the intestines by cholera toxin–expressing strains of the waterborne enteric bacterium V. cholerae . An outbreak can arise suddenly, especially in vulnerable populations with compromised sanitation infrastructure, as in the devastating 2010 outbreak in Haiti. 1 In 2012 alone, V. cholerae infected 3 million to 4 million people, killing nearly 100,000. 2 Although all pathogenic V. cholerae strains possess a similar genomic backbone that may have facilitated adaptation to human intestinal mucosa, 3 , 4 the predominant pathogenic strain, serogroup O1, harbors two genetically distinct biotypes: classical and El Tor (for descriptions of these and . . .